Effect of metformin pretreatment on myocardial injury during coronary artery bypass surgery in patients without diabetes (MetCAB): a double-blind, randomised controlled trial. Issue 8 (August 2015) - El Messaoudi, Saloua; Nederlof, Rianne; Zuurbier, Coert J; van Swieten, Henry A; Pickkers, Peter; Noyez, Luc; Dieker, Hendrik-Jan; Coenen, Marieke J; Donders, A Rogier T; Vos, Annemieke; Rongen, Gerard A; Riksen, Niels P
Summary: Background: During coronary artery bypass graft (CABG) surgery, ischaemia and reperfusion damage myocardial tissue, and increased postoperative plasma troponin concentration is associated with a worse outcome. We investigated whether metformin pretreatment limits cardiac injury, assessed by troponin concentrations, during CABG surgery in patients without diabetes. Methods: We did a placebo-controlled, double-blind, single-centre study in an academic hospital in Nijmegen (Netherlands) in adult patients without diabetes undergoing an elective on-pump CABG procedure. We randomly assigned patients (1:1) in blocks of ten via a computer-generated randomisation sequence to either metformin hydrochloride (500 mg three times per day) or placebo (three times per day) for 3 days before surgery. The last dose was given roughly 3 h before surgery. Patients, investigators, trial staff, and the statistician were all masked to treatment allocation. The primary endpoint was the plasma concentration of high-sensitive troponin I at 6, 12, and 24 h postreperfusion after surgery, analysed in the per-protocol population with a mixed-model analysis using all these timepoints. Secondary endpoints included the occurrence of clinically relevant arrhythmias within 24 hours after reperfusion, the need for inotropic support, time to detubation, duration of stay in the intensive-care unit, and postoperative use of insulin. This study is registered with ClinicalTrials.gov, number NCT01438723 . Findings: Between Nov 8, 2011, and Nov 22, 2013, we randomly assigned 111 patients to treatment (57 to metformin and 54 to placebo). Five patients dropped out from the metformin group, and six from the placebo group. 52 patients in the metformin group and 48 patients in the placebo group were included in the per-protocol analysis. Geometric mean high-sensitivity troponin I increased from 0 μg/L to 3·67 μg/L (95% CI 3·06–4·41) with metformin and to 3·32 μg/L (2·75–4·01) with placebo at 6 h after reperfusion; 2·84 μg/L (2·37–3·41) and 2·45 μg/L (2·02–2·96), respectively, at 12 h; and to 1·77 μg/L (1·47–2·12) and 1·60 μg/L (1·32–1·94) at 24 h. The concentrations did not differ significantly between the groups (difference 12·3% for all timepoints [95% CI −12·4 to 44·1] p=0·35). Occurrence of arrhythmias did not differ between groups (three [5·8%] of 52 patients who received metformin vs three [6·3%] of 48 patients who received placebo; p=1·00). There was no difference between groups in the need for inotropic support, time to detubation, duration of stay in the intensive-care unit, or postoperative use of insulin. No patients died within 30 days after surgery. Occurrence of gastrointestinal discomfort (mostly diarrhoea) was significantly higher with metformin than with placebo (11 [21·2%] of 52 vs two [4·2%] of 48 patients; p=0·01). Interpretation: Short-term metformin pretreatment, although safe, does not seem to be an effective strategy to reduce periprocedural myocardial injury in patients without diabetes undergoing CABG surgery. Funding: Netherlands Organisation for Health Research and Development and Netherlands Heart Foundation.